Sofosbuvir‐based treatment of hepatitis C with severe fibrosis (METAVIR F3/F4) after liver transplantation. Issue 10 (October 2016) - Dumortier, Jérôme; Leroy, Vincent; Duvoux, Christophe; de Ledinghen, Victor; Francoz, Claire; Houssel‐Debry, Pauline; Radenne, Sylvie; d'Alteroche, Louis; Fougerou‐Leurent, Claire; Canva, Valérie; di Martino, Vincent; Conti, Filomena; et al.
Abstract : Recurrence of hepatitis C virus (HCV) after liver transplantation (LT) can rapidly lead to liver graft cirrhosis and, therefore, graft failure and retransplantation or death. The aim of the present study was to assess efficacy and tolerance of sofosbuvir (SOF)–based regimens for the treatment of HCV recurrence in patients with severe fibrosis after LT. The Compassionate Use of Protease Inhibitors in Viral C Liver Transplantation (CULPIT) study is a prospective multicenter cohort including patients with HCV recurrence following LT treated with second generation direct antivirals. The present study focused on patients included between October 2013 and November 2014 and diagnosed with HCV recurrence and liver graft extensive fibrosis (METAVIR F3/F4). A SOF‐based regimen was administered to 125 patients fulfilling inclusion criteria. The median delay from LT was 95.9 ± 69.6 months. The characteristics of patients were as follows: mean age, 59.4 ± 9.0 years; 78.4% male; infected by HCV genotype 1: 78.2%, mean HCV RNA: 6.1 ± 1.0 log10 IU/mL. Eighty patients had failed previous post‐LT antiviral therapy (64.0%) including triple therapy with first generation protease inhibitors in 19 (15.2%) patients. The main combination regimen was SOF/daclatasvir (73.6%). Ribavirin was used in 60 patients. Sustained virological response 12 weeks after treatment was 92.8% (on an intention‐to‐treat basis); 7 patients with virological failure were observed. Serious adverse events occurred in 25.6% of the patients during antiviral treatment. During antiviral treatment and follow‐up, 3 patients were retransplanted and 4 patients died. In conclusion, SOF‐based antiviral treatment shows very promising results in patients with HCV recurrence and severe fibrosis after LT. Liver Transplantation 22 1367–1378 2016 AASLD .